The Policy Implementation of Integrated Service Unit at Universitas Negeri Manado - Warokka, Djoly Vekky; Langkai, Jeane E.; Kandou, Selpius (Technium Social Sciences Journal, 2024)
It is the human right of students as citizens and residents to receive services in accordance with their rights so that they are served quickly, precisely, with quality, without discrimination, and create certainty and satisfaction for service recipients as well as strengthening performance accountability for the public services provided. This research aims to interpret, describe, and analyze the Implementation of the Integrated Service Unit (ULT) Implementation Policy at Universitas Negeri Manado (Unima) and what factors cause the Integrated Service Unit implementation policy not to be implemented according to policy. The research method used is a qualitative method with data collection techniques in the form of observation, interviews, and documentation. The research results show that the implementation of the policy for implementing the Integrated Service Unit at Unima has not been carried out optimally. The influencing factors are 1) The policy for implementing integrated Service Units has not been socialized to students and management staff in study programs and departments that process comprehensive exam requirements; 2) There has not been communication between the integrated service unit staff and students and management staff in study programs and departments who process comprehensive exam requirements; 3) There are not yet sufficient human resources to support the implementation of the Integrated Service Unit; 4) There is no real commitment from structural officials to support the implementation of the Integrated Service Unit.